Can Tourism be Sustainable? An International Perspective - Chakraborty, Rupsha; Chand, Dipannita (Problemy Ekorozwoju, 2026)
Sustainability and tourism have had a long-standing relationship. Tourism as an industry has shifted towards making sustainable choices and implementing policies to align with the Sustainable Development Goals. However, this relationship has layers of complexities and is paradoxical in nature. Practising one within the other is a difficult task, as tourism, primarily, is driven by consumption and economic prosperity, sustainability propagates production, inclusivity and restraint for a better future. This paper discusses the nuanced relationship that sustainability and its three key tenets, namely economic growth, social inclusion and environmental protection, share with tourism. It proposes a framework of measures to materialise sustainable development goals within the tourism industry in real time and practice and cites examples of such implementations from across the globe. In assessing the dynamism between sustainability and tourism, this paper highlights the need to strike a balance between the two and the significance of newer forms of tourism models, such as regenerative tourism, community-led initiatives, and sustainable practices, which can lead to an equitable and just future.